Graphene/moss biomass/lauryl alcohol composites for thermal energy storage - Sari, Ahmet; Can, Ahmet; Cakir, Esma; Batan, Nevzat; Kolayli, Sevgi; Gençel, Osman; Gençel, Osman; Can, Ahmet (Elsevier Science Sa, 2025)
This study aimed to evaluate Sphagnum palustre moss biomass (MB) as a low-cost and eco-friendly material for effectively encapsulating lauryl alcohol (LOH), with the addition of graphene (G) to enhance thermal conductivity. The porous MB material composed mainly of cellulose and lignin, was used for the first time as a supporting matrix in this context. The LOH was impregnated into MB at various concentrations to achieve a seepage-free composite phase change material (PCM). The microstructure, chemical composition, thermal behavior, and thermal stability of the composite were characterized using Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and thermal conductivity measurements. The composite showed no seepage during the solid-liquid phase transition when the LOH loading was 65 %. At this loading, the latent heat values were 162.62 J/g during melting at 19.30 degrees C and 162.51 J/g during freezing at 19.35 degrees C. Although increasing graphene content slightly reduced enthalpy, it enhanced thermal conductivity by up to 95.45 % by adding 4 % graphene. FTIR results confirmed no new chemical bonding between MB and LOH. The MB/LOH/G composite demonstrated excellent thermal reliability over 600 cycles and strong form-stability. These findings suggest that the MB/LOH/G system holds significant promise for use in energy-efficient construction materialsmaterials such as plaster, wall board, concrete, insulation, etc for thermal management of buildings.
Keywords: Phase-Change Materials; Conductivity Enhancement; Lauric Acid; Carbon; Adsorption; Straw